Corelation Perception, Learning, and Motivation with Clinical Nursing Students Caring Behaviour - Mufidah, Alfi Rahmawati; Sukartini, Tintin; Hidayati, Laily (Universitas Airlangga, 2019)
Introduction: Caring behavior is important for a nurse, but nursing students in the stage implementation and the theory who got in academic. The purpose of this research was to identify the relationship of perception, learning, and motivation with caring behaviour.Method: Descriptive research analytical design with cross sectional approach. The population was Regular Nursing Students in Faculty of Nursing Airlangga University. Using a sample of 100 respondents from 112 students, through simple random sampling. . The independent variables in this study: perception, learning, and motivation. The dependent variable was caring behavior. Data were collected by using modified questionnaires for independent variables and observation checklist for caring behavior, modified of Middle Range of Caring Theory Swanson. Data were analyzed by using logistic regression analysis with the degree of significance p < 0.05.Results: The results showed perception (p=0,023), learning (p=0,043) and motivation (p=0.007 related to the behavior of caring.Conclusion: The higher levels of student perception, learning, and motivation then the higher the caring behaviour.